A New Species of the Genus Madahoplia (Coleoptera, Scarabaeidae, Melolonthinae, Hopliini) from Madagascar - B. M. Vasko (Zoodiversity)
An illustrated description and diagnosis of Madahoplia dolini sp. n. and an updated key to the species group III of Madahoplia Lacroix, 1998 are provided. The new species is similar to M. oculata Lacroix differing by the distinctly serrated pronotum, strongly elongated anterior angles and dorsum with whitish- and dark grey scales.